WORK OF AYMARA WOMEN AS AGENTS OF CHANGE AND DEVELOPMENT, A VIEW FROM ANDEAN RURALITY - Javier Santos Puma Llanqui; Reyna Milagros Vilca Mamani; Duverly Joao Incacutipa Limachi; Olimpia Tintaya Choquehuanca; Cleida Incacutipa Limachi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The present research makes visible the historical process of the participation of Aymara women as agents involved in rural development, both in the family environment and in the communal context. The method used was qualitative, using as a technique the participant observation, in-depth interview and the focus group. Twenty-seven family mothers from the Aymara communities of the Puno region participated in the study. From the testimonies we identify the various roles they play in the family environment, as well as their participation in multiple activities and responsibilities in the development of the community. Recognizing the fundamental role, it plays in the preservation of living culture, the importance of economic and family security and the vision of the future that they build and share alongside the family.